Chemical, nutritional and sensory profiles of different pigmented rice varieties impacted by cooking process (Research, Society and Development, 2022)
Pigmented rice has several health benefits associated with the presence of bioactive compounds and its hypoallergenic properties. The cooking process, as it involves high temperatures, can cause changes in the phytochemical and antioxidant profile. Thus, the objective was to study the nutritional and sensory properties of pigmented rice, the effect of the cooking process, comparing black and red rice genotypes developed by the Institution of Agricultural Research and Rural Extension of Santa Catarina (Epagri) to commercial varieties found in the Brazilian market. Epagri´s black rice had higher levels of protein, fat, ash, fiber and fatty acids than commercial black rice. The levels of phenolic compounds and antioxidants were higher in the Epagri rice genotypes than in the commercial varieties for both pigmented rice. When comparing both pigmented rice, black rice showed higher chemical composition, phytochemical profile and antioxidant properties than red rice. Cooking did not affect commercial black rice phenolic and caused a 28% reduction in Epagri black rice, while red rice reduced 60%. Flavonoids reduced 50% in commercial and Epagri genotypes after cooking. Proanthocyanidins were reduced by 79 and 64% in commercial and Epagri red rice, respectively, and anthocyanins were reduced by 56 and 51% in commercial and Epagri black rice, respectively. Regarding the sensory analysis, raw and cooked pigmented rice showed 70 and 80% of acceptability, respectively.